Immediate release tablet formulation of varenicline salicylate and comparative pharmacokinetic study in human volunteers - Kwak SS; Lee ES; Yoon HY; Kim CH; Goo YT; Kang MJ; Lee S; Lee BS; Jeon HR; Oh CH; Choi YW (Dove Medical Press, 2018)
Seong Shin Kwak,1,* Eun Seok Lee,1,* Ho Yub Yoon,1 Chang Hyun Kim,1 Yoon Tae Goo,1 Myung Joo Kang,2 Sangkil Lee,3 Bong Sang Lee,4 Hong Ryeol Jeon,4 Chang Hyun Oh,5 Young Wook Choi1 1College of Pharmacy, Chung-Ang University, Heuksuk-ro, Dongjak-gu, Seoul 06974, Republic of Korea; 2College of Pharmacy, Dankook University, Dandae-ro, Dongnam-gu, CheonanChungnam 31116, Republic of Korea; 3College of Pharmacy, Keimyung University, Dalgubeol-daero, Daegu 42601, Republic of Korea; 4CTCBIO INC., Hyundaikia-ro, Paltan, Hwaseong, Gyeonggi 18576, Republic of Korea; 5Center for Biomaterials, Korea Institute of Science & Technology (KIST), Hwarang-ro, Seongbuk-gu, Seoul 02792, Republic of Korea *These authors contributed equally to this work Purpose: To develop an immediate release-type tablet containing varenicline salicylate (VRC-S), a smoking cessation agent, formulation and stability studies were performed. The in vitro dissolution and in vivo pharmacokinetic (PK) behavior of the tablets were compared with those of the commercial product (Champix) as a reference. Materials and methods: The characteristics of the powder were investigated by particle morphology, size distribution, solubility, hygroscopicity, differential scanning calorimetry, and powder X-ray diffraction. Based on the drug–excipient compatibility test, different VRC-S tablets were prepared with the selected excipients through direct compression or wet granulation method and subjected to a dissolution test. The stability of the most promising VRC-S tablet (F4) was evaluated under accelerated conditions (40°C and 75% relative humidity). Further, the dissolution and human pharmacokinetic profiles of the F4 tablet and Champix were compared. Results: VRC-S showed a positively skewed unimodal size distribution with a specific surface area of 2.02 m2/g, single endothermic peak of 225.2°C in differential scanning calorimetry, crystalline internal structure in powder X-ray diffraction, aqueous solubility of 244.7 mg/mL, and hygroscopicity of 0.256 mg/g. The wet granulation method was preferred for tablet preparation and employed the following excipients: microcrystalline cellulose and anhydrous dibasic calcium phosphate as diluents, croscarmellose sodium as a disintegrant, and colloidal silicon dioxide and magnesium stearate as lubricants. The F4 tablet was stable for 6 months under accelerated conditions. The dissolution of VRC was pH independent, revealing f2 values of 76.49 and 68.38 at pH 1.2 and pH 6.8, respectively. After the oral administration of F4 tablet and Champix to healthy human volunteers, pharmacokinetic parameters, including time to reach the maximum plasma concentration (Tmax), maximum plasma concentration (Cmax), and area under the curve from 0 to infinity (AUCinf), were compared. The values of 90% CI were 0.972–1.035 for Cmax and 0.982–1.075 for AUCinf, which was indicative of the bioequivalence of both products. Conclusion: VRC-S–containing F4 tablet might be a good candidate for smoking cessation treatment. Keywords: varenicline salicylate, smoking cessation, formulation, stability, dissolution, bioavailability